1981
DOI: 10.1017/s0043174500025935
|View full text |Cite
|
Sign up to set email alerts
|

Selective Weed Control with EPTC-Treated Seed of Alfalfa (Medicago sativa)

Abstract: EPTC (S-ethyl dipropylthiocarbamate) was applied to seed of alfalfa (Medicago sativaL.) that was coated with a porous material consisting principally of lime or gypsum. When the treated seed was planted in the field or greenhouse, grass was controlled selectively. When seeds, each carrying 0.1 mg EPTC, were seeded 1 cm apart in rows, the rate of EPTC would have been 2 kg/ha if this quantity of EPTC had been distributed in a band 5 cm wide. Such applications controlled grass completely in bands 5 to 6 cm wide. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1983
1983
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…The consistent control of grass seedlings in bands 2 to 4 em wide when EPTC -treated alfalfa seed was seeded in rows (3) indicates that EPTC consistently moved away from the treated seed rapidly. EPTC controls barnyardgrass by entering the emerging shoot (1).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The consistent control of grass seedlings in bands 2 to 4 em wide when EPTC -treated alfalfa seed was seeded in rows (3) indicates that EPTC consistently moved away from the treated seed rapidly. EPTC controls barnyardgrass by entering the emerging shoot (1).…”
Section: Discussionmentioning
confidence: 95%
“…Recently, Dawson (2,3) demonstrated that alfalfa tolerates exposure to extremely high concentrations of EPTC applied close to the sown seed or directly to the seed before sowing. Although such applications initially expose alfalfa to rates of EPTC as great as 250 times normal, the seedlings were not injured appreciably more than from conventional applications.…”
Section: Introductionmentioning
confidence: 99%
“…Commercial seed treatments with fungicides or insecticides are commonly used in modern agriculture. In contrast, several cases of the use of herbicide-treated seeds have been reported only for control of alfalfa (Medicago sativa L.) (Dawson 1981(Dawson , 1987, grass weeds (Dale 1983), and witchweed (Striga spp.) in cowpea (Vigna unguiculata L.) (Berner et al 1994(Berner et al , 1997 or maize (Zea mays L.) (Kanampiu et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Thiocarbamate herbicides, first synthesized in 1954, have been utilized to control perennial grasses, including bermudagrass, in a variety of agronomic crops (Csinos et al 2000;Dawson 1981;Grey 1975;Harvey et al 1987). These herbicides are highly volatile, which necessitates their incorporation immediately after application (Ashton and Crafts 1981).…”
mentioning
confidence: 99%